(untitled) (Memorias Sifored - Encuentros Educación UAN, 2021)
The following writing allows to count and evaluate the process adapted for the teaching of preschool students during the pandemic that took place in 2020; Taking into account that the teaching of basic sciences had been taught in person and the technological resources in the classrooms were extended to the remote use of audiovisual media on a non-continuous basis, screens were not a matter of concern, cell phones, tablets and Other resources were prohibited in educational establishments for both teachers and students, today they are their maximum teaching and learning resource. For many, the action of educating through a screen usually seems simple since they link the idea with tutorials or explanatory videos found in different applications and audiovisual programs, however, teachers, students and parents were not prepared for this, in No educational establishment, be it school or university, is directed to teach in the event of a pandemic, which is why more than a pedagogical strategy or evaluation of educational innovation, it should be counted as the challenge that made us change the way of re-educating a whole society from one screen. Today, a short time after the end of a school year, we can rescue the resources, the strategies, the new ways of teaching and above all value the human beings who from one day to the next modified their home as a classroom, changed the decorative pictures by visual aids and adapted to a new reality.